Mediating Role of Psychological Capital in Relationship between Occupational Stress and Turnover Intention among Nurses at Veterans Administration Hospitals in Korea - Hee-Yun Yim, RN, MSc; Hyun-Ju Seo, RN, MPH, PhD; Yoonhyung Cho, PhD; JinHee Kim, RN, MPH, PhD (Elsevier, 2017)
Purpose: The aim of this study was to evaluate the mediating role of psychological capital (PCP) in the relationship between occupational stress and turnover intention in nurses. Methods: Data were collected from a sample of 447 nurses working at four Veterans Administration Hospitals throughout South Korea from July 1 to July 31, 2014. We collected data from the nurses using the following surveys: the Short Form Korean-Occupational Stress Scale, the Korean version of the Turnover Intention Scale, and the Korean version of the Psychological Capital Questionnaire. Multiple linear regression analysis was performed to examine the mediating role of PCP. Results: The level of occupational stress was 1.81 ± 0.23, the level of turnover intention was 3.29 ± 0.86, and the PCP level was 3.95 ± 0.52. There were significant correlations among the three variables (occupational stress, turnover intention, and PCP). PCP played a partial mediating role (β=−0.22, p=.008) in the relationship between occupational stress and turnover intention (p<.001) among nurses working at the Veterans Administration Hospitals. Conclusion: Based on the findings of this study, we recommend that South Korean hospitals offer occupational stress management programs that incorporate relevant programs in efforts to strengthen the overall components of PCP among nurses to reduce turnover intentions. Further studies are required to determine the most effective intervention programs for hospital settings.